Characterization of drug‐induced transcriptional modules: towards drug repositioning and functional understanding. Issue 1 (30th April 2013) - Iskar, Murat; Zeller, Georg; Blattmann, Peter; Campillos, Monica; Kuhn, Michael; Kaminska, Katarzyna H; Runz, Heiko; Gavin, Anne‐Claude; Pepperkok, Rainer; van Noort, Vera; Bork, Peer
<x xml:space="preserve">Abstract</x> In pharmacology, it is crucial to understand the complex biological responses that drugs elicit in the human organism and how well they can be inferred from model organisms. We therefore identified a large set of drug‐induced transcriptional modules from genome‐wide microarray data of drug‐treated human cell lines and rat liver, and first characterized their conservation. Over 70% of these modules were common for multiple cell lines and 15% were conserved between the human in vitro and the rat in vivo system. We then illustrate the utility of conserved and cell‐type‐specific drug‐induced modules by predicting and experimentally validating (i) gene functions, e.g., 10 novel regulators of cellular cholesterol homeostasis and (ii) new mechanisms of action for existing drugs, thereby providing a starting point for drug repositioning, e.g., novel cell cycle inhibitors and new modulators of α‐adrenergic receptor, peroxisome proliferator‐activated receptor and estrogen receptor. Taken together, the identified modules reveal the conservation of transcriptional responses towards drugs across cell types and organisms, and improve our understanding of both the molecular basis of drug action and human biology.